URB597 induces subtle changes to aggression in adult Lister Hooded rats - Warren, William G.; Hale, Ed; Papagianni, Eleni P.; Cassaday, Helen J.; Stevenson, Carl W.; Stubbendorff, Christine (Frontiers in Psychiatry, 2022)
The endocannabinoid system has been implicated in both social and cognitive processing. The endocannabinoid metabolism inhibitor, URB597, dose-dependently improves non-social memory in adult Wistar and Sprague Dawley rats, whereas its effect on social interaction (SI) is affected by both rat strain and drug dose. Lister Hooded rats consistently respond differently to drug treatment in general compared with albino strains. This study sought to investigate the effects of different doses of URB597 on social and non-social memory in Lister Hooded rats, as well as analysing the behavioural composition of the SI. Males were tested for novel object recognition (NOR), social preference (between an object and an unfamiliar rat), social novelty recognition (for a familiar vs unfamiliar rat) and SI with an unfamiliar rat. URB597 (0.1 or 0.3 mg/kg) or vehicle was given 30 minutes before testing. During SI testing, total interaction time was assessed along with time spent on aggressive and explorative behaviours. Lister Hooded rats displayed expected non-social and social memory and social preference, which was not affected by URB597. During SI, URB597 did not affect total interaction time. However, the high dose increased aggression, compared to vehicle, and decreased anogenital sniffing, compared to the low dose of URB597. In summary, URB597 did not affect NOR, social preference or social recognition memory but did have subtle behavioural effects during SI in Lister hooded rats. These findings highlight the importance of considering strain as well as the composition of behaviour when investigating drug effects on social behaviour.